Immobilized Soybean Peroxidase Hybrid Biocatalysts for Efficient Degradation of Various Emerging Pollutants - Morsi, Rana (Biomolecules, 2021)
In the present study, soybean peroxidase (SBP) was covalently immobilized onto two functionalized photocatalytic supports (TiO(2) and ZnO) to create novel hybrid biocatalysts (TiO(2)-SBP and ZnO-SBP). Immobilization caused a slight shift in the pH optima of SBP activity (pH 5.0 to 4.0), whereas the free and TiO(2)-immobilized SBP showed similar thermal stability profiles. The newly developed hybrid biocatalysts were used for the degradation of 21 emerging pollutants in the presence and absence of 1-hydroxy benzotriazole (HOBT) as a redox mediator. Notably, all the tested pollutants were not equally degraded by the SBP treatment and some of the tested pollutants were either partially degraded or appeared to be recalcitrant to enzymatic degradation. The presence of HOBT enhanced the degradation of the pollutants, while it also inhibited the degradation of some contaminants. Interestingly, TiO(2) and ZnO-immobilized SBP displayed better degradation efficiency of a few emerging pollutants than the free enzyme. Furthermore, a combined enzyme-chemical oxidation remediation strategy was employed to degrade two recalcitrant pollutants, which suggest a novel application of these novel hybrid peroxidase-photocatalysts. Lastly, the reusability profile indicated that the TiO(2)-SBP hybrid biocatalyst retained up to 95% degradation efficiency of a model pollutant (2-mercaptobenzothiazole) after four consecutive degradation cycles.